simplify the expression 16+7y-8 rewrite as 7(y-8)7•y= 7y 7•8= 56 7y-56 = -49y answer= 16+ (-49y)
Chat with our AI personalities
16+7y-8 = 7y+16-8 = 7y+8
5y+8 = 7y-6 5y-7y = -6-8 -2y = -14 y = 7
So Hey, Step 1: 7y=7y :) Step 2: 7y/7y=49^8 :) Step 3: 49^8/ = *6r1 :) So Hey Again so like you saw all the steps right?? Ok, GOOD :)............................................................................................................................................................................................................. So the reciprocal of 7y is 6^1 :)
Ghs
It cannot be simplified any further, so it is: 2x + 7y